Estimation of planning organ at risk volumes for ocular structures in dogs undergoing three‐dimensional image‐guided periocular radiotherapy with rigid bite block immobilization. Issue 2 (18th January 2021) - Wolf, Friederike; Rohrer Bley, Carla; Besserer, Jürgen; Meier, Valeria
Abstract: Planning organ at risk volume (PRV) estimates have been reported as methods for sparing organs at risk (OARs) during radiation therapy, especially for hypofractioned and/or dose‐escalated protocols. The objectives of this retrospective, analytical, observational study were to evaluate peri‐ocular OAR shifts and derive PRVs in a sample of dogs undergoing radiation therapy for periocular tumors. Inclusion criteria were as follows: dogs irradiated for periocular tumors, with 3D‐image‐guidance and at least four cone‐beam CTs (CBCTs) used for position verification, and positioning in a rigid bite block immobilization device. Peri‐ocular OARs were contoured on each CBCT and the systematic and random error of the shifts in relation to the planning CT position computed. The formula 1.3×Σ+0.5xσ was used to generate a PRV of each OAR in the dorsoventral, mediolateral, and craniocaudal axis. A total of 30 dogs were sampled, with 450 OARs contoured, and 2145 shifts assessed. The PRV expansion was qualitatively different for each organ (1‐4 mm for the dorsoventral and 1‐2 mm for the mediolateral and craniocaudal axes). Maximal PRV expansion was ≤4 mm and directional for the majority; most pronounced for corneas and retinas. Findings from the current study may help improve awareness of and minimization of radiation dose in peri‐ocular OARs for future canine patients. Because some OARs were difficult to visualize on CBCTs and/ or to delineate on the planning CT, authors recommend that PRV estimates be institution‐specific and applied with caution.